The Survey of the Relationship between Auditing Quality and the Profitability in the Companies Accepted in Tehranas Exchange Market (Global Journal of Management and Business Research, 2016)
The present study deals with the evaluation of the relationship between auditing quality and the profitability in the companies accepted in Tehran's securities exchange market. To determine the auditing quality there has been made use of two scales of auditor size (DeAngelo, L.E., 1981) and the auditor's tenure period (Myers, J.N., Myers, L.A. & Omer, T.C., 2003). The total number of 52 companies accepted in Tehran's securities exchange market has been surveyed. The study findings show that generally there is a positive and weak relationship between the auditor size (auditor's good fame) and the auditor's tenure period and the profitability ratios. To survey the auditor's size the member auditing institutions of the formal accountant society are regarded as small auditing firms and accounting organization due to the great many staff members working in it and also due to their long working history is considered as the big auditing institution.
Keywords: auditing quality; auditor2019; s tenure period; auditor2019; s size; profitability ratios and tehran2019; s securities exchange market